2019
DOI: 10.1097/md.0000000000016236
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotic syndrome associated with ramucirumab therapy

Abstract: Ramucirumab is a human immunoglobulin G1 monoclonal antibody that binds to vascular endothelial growth factor receptor 2 and is used for the treatment of metastatic or inoperable gastric, colorectal, and non-small cell lung cancers. However, ramucirumab can result in renal adverse events, including nephrotic syndrome, and the clinical course of this event is unclear. This study aimed to investigate the clinical course and pathological findings of patients with nephrotic syndrome after ramucirumab treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 27 publications
1
15
0
2
Order By: Relevance
“…Previous studies suggested that RTKI inhibits NF-κB activity, leading to c-mip overexpression, and induces MCD or FSGS. 5 In two previous studies on ramucirumab-induced nephropathy, three cases of renal pathology were reported 3 8 and all of them were reported as TMA. The development of renal impairment characterised the three previous cases after switching from bevacizumab to ramucirumab, as in this case.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies suggested that RTKI inhibits NF-κB activity, leading to c-mip overexpression, and induces MCD or FSGS. 5 In two previous studies on ramucirumab-induced nephropathy, three cases of renal pathology were reported 3 8 and all of them were reported as TMA. The development of renal impairment characterised the three previous cases after switching from bevacizumab to ramucirumab, as in this case.…”
Section: Discussionmentioning
confidence: 99%
“… 7 Although other VEGF inhibitory drugs, such as the anti-VEGF monoclonal body (bevacizumab), tyrosine kinase inhibitors (sunitinib, axitinib, sorafenib and cediranib) and VEGF-Trap (aflibercept) have been known to cause nephrotic-range proteinuria and renal dysfunction, ramucirumab has been reported in only one case report 8 and one single-centre case report. 3 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fujii и соавт. описали 5 случаев нефротического синдрома после введения 1-2 доз рамуцирумаба [44]. Продолжительность лечения до появления нефротического синдрома составила от 21 до 112 (в среднем 46) дней.…”
Section: äàííûå ìîðôîëîãè÷åñêèõ èññëåäîâàíèéunclassified